Morphogenic correlation between facial form and intercanine width - an aid in forensic dentistry - S Sivaranjani; V Krishna Mohan; G Nimoshini; Bose Divya; V Vasanthi; Ramya Ramadoss (SRM Journal of Research in Dental Sciences, 2021)
Background: Forensic odontology is a branch of forensic dentistry that utilizes dental remains for personal identification. When facial recognition is not possible, the facial form of the person can be reconstructed with the help of teeth present and dental structures available. The teeth in the maxillary intercanine region play a vital role for the same. The intercanine width varies considerably between different populations and races and its relation with other facial parameters can be used in personal identification and even facial reconstruction. Aim: The aim of the present study is to assess the correlation between the tooth form and face form by correlating the intercanine width with other facial parameters such as interpupillary distance, interalar distance, interzygomatic distance, and intercanthus distance in the Ethnic Tamil population. Materials and Methods: The study was conducted on a sample of 100 patients aged between 20 and 40 years. Five parameters, namely the intercanine width, interpupillary width, interalar distance, interzygomatic distance, and intercanthus distance was measured using a digital Vernier caliper. The data obtained were tabulated and analyzed using SPSS statistical analysis software. Unpaired t-test was used to compare the mean values of the parameters among males and females. Pearson's correlation was run to assess the relationship between the parameters and P < 0.05 was considered to be statistically significant. Results: Among 100 participants, 50 were male and 50 were female. The mean intercanine width of males (35.1 mm ± 3.8) and females (33.1 mm ± 3.1), mean interzygomatic distance of males (110.8 mm ± 12.3) and females (106.7 mm ± 8.1), and mean interalar distance of males (26.2 mm ± 5.8) and females (28.3 mm ± 4.5) were found to be statistically significant. There was a significant, moderate correlation (r = −0.3; P < 0.05) between the intercanine and intercanthus width in males but not in females. Conclusion: In the present study, a weak correlation existed between intercanine distance and other facial parameters. Several parameters determine the facial form and a combination of these parameters have to be considered thereby reconstruction of the face is possible for future prospectus in forensic dentistry.